Effects of Early and Current Environmental Enrichment on Behavior and Growth in Pigs - Luo, Lu; Reimert, Inonge; Middelkoop, Anouschka; Kemp, Bas; Bolhuis, J. Elizabeth (Frontiers in Veterinary Science, 2020)
Enriched environments are known to beneficially affect the behaviour of pigs, as compared with barren pens. The influence of enrichment may, however, depend on pigs’ early life housing experiences. Aim of this study was to investigate the (long-term) effects of early and later life environmental enrichment on behaviour and growth in pigs with different coping styles. Pigs were housed in either barren pens or in larger pens enriched with rooting substrates from birth, and half of them experienced a housing switch, i.e. a loss or gain of enrichment, at 7 weeks of age, creating four treatment groups. Home pen behaviour and body weight were recorded until 19 weeks of age. Pigs were classified as reactive or proactive based on a backtest at two weeks of age. Enrichment increased time spent exploring, chewing and play, and decreased damaging behaviours and pen-directed exploring and chewing. Behaviour of pigs that switched from barren to enriched pens or vice versa reflected not only their actual environment, but also their early life housing conditions. Effects of early and later life enrichment on most behaviours were in opposite direction. Therefore, effects of (lack of) enrichment after the switch were more pronounced in pigs that had experienced a different early life condition. For instance, pigs experiencing an upgrade from barren to enriched pens seemed to ‘catch-up’ by showing more exploration and play. Conversely, pigs exposed to a downgrade displayed more oral manipulation of pen mates than ones kept barren throughout, which particularly held for pigs with a reactive coping style. Effects of early life and current housing on several other behaviours depended on coping style too. Pigs housed in enriched conditions appeared better able to cope with weaning, as they gained more weight and had higher feed intake post-weaning. Barren housed pigs had a lower body weight than enriched pigs just before the switch, after which growth was mainly determined by actual housing, with enriched kept pigs having a higher feed intake and body weight. Thus, not only current housing conditions, but also a (mis)match with the early life environment may affect behaviour and growth of pigs.